2022
DOI: 10.1007/s11356-022-22700-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of house dust trace elements and human exposure in Ankara, Turkey

Abstract: One of the impacts of the COVID-19 pandemic is leading people remain at homes longer than ever. Considering the elongation of the time people spend indoors, the potential health risks caused by contaminants including heavy metals in indoor environments have become even more critical. The purpose of this study was to evaluate the levels and sources of heavy metals in indoor dust, to assess the exposure to heavy metals via indoor dust, and to estimate the associated health risk. The highest median value was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 87 publications
0
0
0
Order By: Relevance
“…These findings reveal that there is no strong influence of different heating systems on the concentrations of Zn found in the analyzed dust samples. The average concentration of Zn obtained in this study was higher than those found in the Kingdom of Saudi Arabia [57], China [38], Turkey [26], and Malaysia [56], but lower than those found in Australia [54], Egypt [55], Canada [58], and Jordan, Amman city [43] as shown in Table 4.…”
Section: Zinc (Zn)contrasting
confidence: 68%
See 4 more Smart Citations
“…These findings reveal that there is no strong influence of different heating systems on the concentrations of Zn found in the analyzed dust samples. The average concentration of Zn obtained in this study was higher than those found in the Kingdom of Saudi Arabia [57], China [38], Turkey [26], and Malaysia [56], but lower than those found in Australia [54], Egypt [55], Canada [58], and Jordan, Amman city [43] as shown in Table 4.…”
Section: Zinc (Zn)contrasting
confidence: 68%
“…The author reported in his study that the type of heating system (e.g., wood/olive residue, kerosene, natural gas, and central heating) has a significant impact on the concentrations of the studied metals found in the house dust samples collected from Ajlune city, Jordan [24]. Compared to other studies, the average concentration of Pb in this study was higher than those found in Malaysia [56], Kingdom of Saudi Arabia [57], Turkey [26], China [38], and Jordan, Al-Karak city [25], but lower than those found in Egypt [55], Australia [54], Canada [58], and Jordan, Amman city [43] as described in Table 4.…”
Section: Lead (Pb)contrasting
confidence: 51%
See 3 more Smart Citations